2011
DOI: 10.1007/s10916-011-9762-6
|View full text |Cite
|
Sign up to set email alerts
|

Design Ensemble Machine Learning Model for Breast Cancer Diagnosis

Abstract: In this paper, we classify the breast cancer of medical diagnostic data. Information gain has been adapted for feature selections. Neural fuzzy (NF), k-nearest neighbor (KNN), quadratic classifier (QC), each single model scheme as well as their associated, ensemble ones have been developed for classifications. In addition, a combined ensemble model with these three schemes has been constructed for further validations. The experimental results indicate that the ensemble learning performs better than individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…First the individual machine learning classification methods are trained, tested and tuned on the database [28,29]. In this work we picked 4 different machine learning methods to use as individual ML methods therefore n = 4: Disjunctive Normal Form (DNF) rule based method (CN2 learner) [5,28], Decision Tree [28,29], Support Vector Machines (SVM) [28,29] and Naïve Bayes [28,29,30]. Each ML classification method goes through training, testing and tuning phases.…”
Section: Adaptive Methods and Stopping Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…First the individual machine learning classification methods are trained, tested and tuned on the database [28,29]. In this work we picked 4 different machine learning methods to use as individual ML methods therefore n = 4: Disjunctive Normal Form (DNF) rule based method (CN2 learner) [5,28], Decision Tree [28,29], Support Vector Machines (SVM) [28,29] and Naïve Bayes [28,29,30]. Each ML classification method goes through training, testing and tuning phases.…”
Section: Adaptive Methods and Stopping Criteriamentioning
confidence: 99%
“…This was the highest accuracy out of all the previous research methods that we found in literature. An ensemble method was tested in 2011 combining the methods Neural Fuzzy, K-Nearest Neighbors, and Quadratic Classifier, resulting in 97.14% accuracy [5]. This ensemble method did not use weights or have a hierarchical system of testing.…”
Section: Introductionmentioning
confidence: 99%
“…It also helps to reduce variance and avoid overfitting, and is generally applied to decision tree methods but can be used with any type of method. The bagging method proceeds according to the procedure depicted in Figure 8 [22,23]. In general, in case of categorical data, the predictor is counted by voting, and in case of continuous data, it is counted by the average.…”
Section: Baggingmentioning
confidence: 99%
“…One of the ensemble classification methods, the bagging method, is another name for bootstrap aggregation. It is generally classified based on a decision tree, and it is a method for changing the number of boosts to improve classification accuracy [22,23]. The k-nearest neighbor (kNN) method is a nonparametric method that was used in statistical applications in the early 1970s.…”
Section: Introductionmentioning
confidence: 99%
“…Hsieh et al [53] have developed and ensemble machine learning model for diagnosing breast cancer. In this model, information-gain has been adopted for feature selection.…”
Section: Related Workmentioning
confidence: 99%